Analysis of Mental Health Messages in BTS’ “Zero O’Clock” Song Lyrics Using Ferdinand de Saussure’s Semiotic Approach - Dina Juniar Anggraini; Pisca Dara Apnaza; Septian Dwi Putri; Maria Maria (Review: Journal of Multidisciplinary in Social Sciences, 2026)
This study aims to analyze the meaning of mental health messages in the lyrics of BTS’s song “Zero O’Clock” using Ferdinand de Saussure’s semiotic theory. This research applies a descriptive qualitative method with a constructivist paradigm. The data were collected through lyric observation, interviews, and literature studies, then analyzed by identifying signifier and signified elements in selected lyric fragments. The results show that “Zero O’Clock” represents mental health messages related to emotional pressure, self-reflection, hope, and the opportunity to start over. The phrase “Zero O’Clock” symbolizes a new beginning, while lyrics such as “And you’re gonna be happy” reflect optimism and emotional recovery. Therefore, this song can be understood as a form of popular music that communicates messages of self-acceptance, resilience, and mental health awareness to its listeners.